Study of Prevalence and Associated Risk Factors of Overweight and Obesity among the Residents of Semi Urban Region of Eastern Nepal (Journal of Nobel Medical College, 2021)
Background: Low-income countries like Nepal experience a double disease burden infectious diseases risk as well as rising incidence of non-communicable diseases .The present cross sectional study assesses the prevalence of overweight and associated factors in ward no. 1 and 3 of Tankisinuwari VDC, Morang.Materials and Methods: A Community based cross sectional study was conducted in ward no. 1 and 3 of Tankisinuwari VDC, Morang. Total 152 (10%) households were selected by systematic random sampling technique and then 590 individuals (male 323 and female 267), with the age ranging from 10 to 70 years were included in the study. Measurement of weight and height was done by calibrated standard weighing scale and measuring tape.Results: The prevalence of overweight was 16.1%  which was significantly more among  male (11.5%)  than in  female ( 4.6%)  while prevalence of obesity was 2.5% , which was significantly more among  female (2.2%),   than male (0.3)%, P